Tantangan Pengembangan Karier dalam Sistem Peradilan Indonesia: Studi Kasus Hakim dan Panitera - Jefri Pratama; Abdul Wahab Hasyim; Husen Alting; Johan Fahri (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
The Constitutional Court and the Supreme Court of the Republic of Indonesia are the two high state institutions that possess judicial authority; they are both independent of other bodies of government. The Supreme Court, in particular, has two main types of human resources—judge (hakim) and Registrar (Panitera). Despite the fact that registrar and judge job descriptions are clearly different according to regulations, career paths indicate otherwise—while a judge can serve as a registrar at the Supreme Court level, a registrar cannot. This study examines career development inconsistencies in Indonesia’s judicial system, focusing on the dual roles of judges and registrars. Using a literature review approach, this paper highlights regulatory ambiguities and the urgent need for policy reform to address career progression challenges within the Supreme Court. This highlights the formation of a case that needs to be further explored by using a case study approach to unveil factors leading to this situation.